2002
DOI: 10.1055/s-2002-29088
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and enzymatic changes of the small intestine in an n0-STZ diabetes rat model

Abstract: Summary. Many studies have shown that experimental type 1 diabetes causes morphological, functional, and metabolic alterations in the small intestine. The more frequent form of the disease, type 2 diabetes, however, has been less studied. Here the influence of diabetes on the functionality of the small intestine was studied in an experimental diabetes model, with a certain degree of residual insulin secretion, specifically in the n0-STZ model. - The diabetic rats in this model were found to have glycaemia leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 16 publications
(22 reference statements)
4
6
0
Order By: Relevance
“…As for LDH activity, results from our experiment show that diabetes decreases LDH activity (Figure 3). These result are similar than Tormo et al [37], but not than Melinkeri et al [38]. A highly significant elevation in the activity of γ-GT was observed in plasma of alloxan-induced diabetic rats.…”
Section: Discussionsupporting
confidence: 89%
“…As for LDH activity, results from our experiment show that diabetes decreases LDH activity (Figure 3). These result are similar than Tormo et al [37], but not than Melinkeri et al [38]. A highly significant elevation in the activity of γ-GT was observed in plasma of alloxan-induced diabetic rats.…”
Section: Discussionsupporting
confidence: 89%
“…Animal tests showed that disaccharidase and lipase activities were higher in diabetic groups than in the normal group. High disaccharidase activities would increase postprandial blood glucose level, leading to impairment of glucose metabolism . Acarbose is a commercial antihyperglycemic drug and an α ‐glucosidase inhibitor, which could decrease postprandial blood glucose level.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand Cai (1989) and Ryder et al (1987) observed decrease in LDH in diabetic subjects, but also, according to Tormo et al (2002), diabetes mellitus did not cause any changes in LDH activity. Opposite to diabetic animals from room temperature we found significant increase in LDH in heat-acclimated ones (Fig.…”
Section: Factorial (Two-way) Anovamentioning
confidence: 88%